The impact of public infrastructure on neighbourhood liveability: a study of residents’ perceptions and satisfaction - Abu Bakar, Nor Azlina; Ujang, Norsidah; Abdul Aziz, Faziawati; Komak, Foroogh Ali (Hasan Mandal On behalf of Istanbul Technical University, 2024)
Urban areas face obstacles hindering services and sustainable development, reducing neighbourhood contentment, and resulting in a lack of dynamism and efficiency. This paper discusses the potential impact of “neighbourhood quality design in terms of public infrastructure provision” on residents’ satisfaction and neighbourhood liveability in Cyberjaya, the smart city of Malaysia. This study aims to investigate the relationship between neighbourhood liveability, public infrastructure provision, and residents’ satisfaction. Data was collected through a public survey and reviewing government reports, and the latest blueprint (Sustainable Smart City Action Plan) of Cyberjaya. The findings shed light on the importance of quality neighbourhood characteristics and its public infrastructure availability in enhancing liveability and resident satisfaction with the neighbourhood as their living area. The findings suggest that despite the availability of basic amenities, residents may experience lower levels of satisfaction and emotional response due to a lack of variations in social infrastructure that foster a sense of community and liveability.